2013
DOI: 10.1186/2049-9256-1-4
|View full text |Cite
|
Sign up to set email alerts
|

NRXN1 deletions identified by array comparative genome hybridisation in a clinical case series – further understanding of the relevance of NRXN1 to neurodevelopmental disorders

Abstract: BackgroundMicrodeletions in the NRXN1 gene have been associated with a range of neurodevelopmental disorders, including autism spectrum disorders, schizophrenia, intellectual disability, speech and language delay, epilepsy and hypotonia.ResultsIn the present study we performed array CGH analysis on 10,397 individuals referred for diagnostic cytogenetic analysis, using a custom oligonucleotide array, which included 215 NRXN1 probes (median spacing 4.9 kb). We found 34 NRXN1 deletions (0.33% of referrals) rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 42 publications
6
33
0
Order By: Relevance
“…17,24 As expected for many of the above-mentioned neurodevelopmental phenotypes, delays in receptive and/or expressive language development have been consistently reported in children with NRXN1 deletions. 13,17,21,23,56 Brignell et al 74 made a comprehensive evaluation of speech and language phenotypes, reporting speech difficulties in 69% of the patients with NRXN1 deletions.…”
Section: Phenotypic Spectrum Of Heterozygous Nrxn1 Exonic Deletionsmentioning
confidence: 99%
“…17,24 As expected for many of the above-mentioned neurodevelopmental phenotypes, delays in receptive and/or expressive language development have been consistently reported in children with NRXN1 deletions. 13,17,21,23,56 Brignell et al 74 made a comprehensive evaluation of speech and language phenotypes, reporting speech difficulties in 69% of the patients with NRXN1 deletions.…”
Section: Phenotypic Spectrum Of Heterozygous Nrxn1 Exonic Deletionsmentioning
confidence: 99%
“…Heterozygous exonic deletions of NRXN1 have been associated with a range of neurodevelopmental and neuropsychiatric phenotypes (Bucan et al, ; Ching et al, ; Curran, Ahn, Grayton, Collier, & Ogilvie, ; Gregor et al, ; Onay et al, ; Rujescu et al, ; Vinas‐Jornet et al, ; Wang & Gong, ; Zweier, ) and are found in about 1 in 500 samples referred for clinical microarray analysis. However, NRXN1 deletions are frequently inherited from a mildly affected or clinically unaffected parent, and are also found in control populations at a frequency of about 1 in 5,000, indicating incomplete penetrance (Ching et al, ; Lowther et al, ; Schaaf et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Speech and language difficulties are expected to be present in many of the above‐mentioned neurodevelopmental phenotypes, and delays in speech and/or language have been reported consistently in children with NRXN1 deletions (Bena et al, ; Ching et al, ; Curran et al, ; Dabell et al, ; Gregor et al, ), yet comprehensive evaluation of speech and language phenotypes has not been reported in these children. Here, we describe the communication phenotypes in 21 children with exonic deletions of NRXN1 , including evaluation of speech production (phonology, articulation, dysarthria, childhood apraxia of speech), oromotor structure and function, receptive and expressive language and pragmatic (social) language ability.…”
Section: Introductionmentioning
confidence: 99%
“…Using the BBGRE tool, we found exonic deletions in the NRXN1 gene, predominantly affecting the alpha isoform, in patients with a range of neurodevelopmental disorders referred for diagnostic cytogenetic analysis (12). Patients have a range of phenotypes including developmental delay, learning difficulties, attention-deficit hyperactivity disorder, autism, speech delay, social communication difficulties, epilepsy, behaviour problems and microcephaly.…”
Section: Methodsmentioning
confidence: 99%